(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article explores the evolution of American linguistic thought throughout the 20th century, focusing on the major theoretical paradigms and methodological shifts that shaped the discipline. It examines the transition from early structuralism, represented by scholars such as Leonard Bloomfield, to the emergence of transformational-generative grammar introduced by Noam Chomsky in the mid-20th century. The study highlights how American linguistics moved from a behaviorist and empiricist framework toward a more cognitive and mentalistic approach, emphasizing the innate aspects of language acquisition. Furthermore, it considers the influence of interdisciplinary developments, including psychology, anthropology, and philosophy, on linguistic theory. Special attention is given to the role of descriptive linguistics in documenting indigenous languages and its impact on linguistic diversity studies. The article also analyzes how sociolinguistics and pragmatics emerged as important subfields toward the latter half of the century, reflecting broader social and cultural concerns. Overall, the research demonstrates that American linguistic thought underwent a profound transformation, laying the foundation for modern linguistic science and continuing to influence contemporary research in language theory and application